The granting of sentence remission to corruption offenders in the perspective of human rights - Beno, Muhammad Ehsan Kelana Putra (Trigin Publisher, 2025)
This study examines the regulation and human rights implications of sentence remission for corruption offenders within Indonesia’s legal system. Remission is recognized as a statutory right granted to prisoners who meet established requirements; however, corruption as an extraordinary crime is subject to stricter regulatory conditions. The discussion analyzes the normative framework provided by Law No. 22 of 2022, implementing regulations, and constitutional provisions, particularly Article 28J of the 1945 Constitution, which allows lawful limitations on human rights. The study incorporates human rights theories by Karel Vasak and John Locke to contextualize the philosophical basis for maintaining prisoners’ residual rights while recognizing the state’s authority to restrict them for legitimate purposes. Findings show that remission embodies both rehabilitative and administrative functions, yet its application to corruption offenders requires careful legal justification to maintain proportionality, safeguard public interest, and uphold human rights principles. The analysis concludes that the regulation of remission must reflect a balanced approach that protects inherent human dignity while supporting the integrity of anti-corruption efforts.